Dyskusja jako jedna z metod nauczania problemowego języka rosyjskiego jako obcego - Dziewanowska, Dorota (Studia Rossica Posnaniensia, 2016)
The author of the article points out the advantages of using the discussion method (which is one of the strategies of problem teaching) during foreign language classes. This strategy creates the possibility to develop various competences in learners, for example: the competence of formulating their own opinion; the competence of expressing their point of view; the competence of achieving consensus and formulating decisions reached through solving the problem together with a group of learners; the competence  of summing up. In the process of foreign language teaching, discussion is the most effective and also the most complicated form of language practice, and one which requires multi-stage preparation.